Literatura surda: estratégias de ensino de fábulas para alunos surdos - Silva, Larissa Jéssica Leão da (Brasil, 2023)
This research aims to present methodologies to improve the teaching-learning process of deaf students using the fable genre. According to the authors Rosa (2011) and Sutton-Spence (2021) Deaf Literature is essential for the development of various capacities that expand knowledge of deaf culture. Deaf Literature opens up opportunities not only for communication, but also serves to expand your worldview. Fernandes (2001), Pimenta (2002) 6 and Karnopp (2009) describe fables as facilitating instruments for expressing feelings, emotions and for teaching human values. In this way, this article presents the methodology of qualitative research, with the performance of analyzes, from questionnaires answered by deaf teachers. Finally, the presented results of the study reaffirm the need to use strategies of visual resources, interactive dynamics and a proposal for an online game prototype, called Fábula e Aprendizagem using the wordwall site.